PENGARUH KONDISI SOSIAL DAN EKONOMI ORANG TUA TERHADAP MOTIVASI MELANJUTKAN PENDIDIKAN KEPERGURUAN TINGGI PADA SISWA KELAS XII SMA NEGERI 2 DUMAI - Kiki Radha Angraini; Henny Indrawati; Herdisyem sabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is done in SMA Negeri 2 Dumai, with the purpose is to analyze how influence of social and economic condition of parents to motivation continuity education of student in XII class of SMA Negeri 2 Dumai. The population in this analyze are all students of XII class SMA Negeri 2 Dumai which amounted to 279 students. Randomly sampling as many as 75 students. Technique of collecting is done through questionnaire technique and using primary and secondary data. The analyzed using hypothesis, simultaneous test (Test F), Coefficient of Determination (R2), partial test (Test t) and multiple linear regression. There are 2 variables ; social and economic condition of parent. The results showed that the influence of social and economic condition of parent are influence to motivation continuity of education of student . This means that the independent variables together affect the dependent variable. Furthermore, based on the partial test (t test) it can be seen that only the variable economic condition of parents affecting the level of education of children is shown with significance 0.011 while other variables have no effect. Every parent is expected to pay attention to their children's education because children who have education usually have a thinking forward pattern for the welness of their families and parents this is crucial role in decision-making for children school.Keywords: Social Condition, Economic Condition, Motivation Continuing Education.